Penegakan Hukum terhadap Penjualan Hewan yang Dilindungi berdasarkan Undang-Undang Nomor 5 Tahun 1990 Tentang Konservasi Sumber Daya Alam dan Ekosistemnya - Anggi Muhammad Fadil; Chepi Ali Firman (UNISBA Press, 2022)
Abstact. Thetrade in protected animals is a criminal act that has a major influence on the balance of the ecosystem of living things in nature. illegal trade in protected animals, one of the impacts is the extinction of these protected animals. The trade in wild animals is said to be illegal if it does not have an official permit from the government and the Natural Resources Conservation Agency. The crime of trafficking has been regulated in Law no. 5 of 1990 concerning the Conservation of Biological Natural Resources and Their Ecosystems. First, to understand the law enforcement of the crime of trafficking in protected animals in the Bandung city area. Second, to understand the policy of the Bandung city government towards the crime of trafficking in protected animals. In this study, the authors used a normative juridical approach. research specifications, this research is descriptive analytical. prioritizing library research to obtain library materials as basic data, which is supported by field research. The result of this study is that law enforcement in various forms aims to ensure that laws and regulations in the field of conservation of living natural resources and their ecosystems can be obeyed by all levels of society and that violators are given strict sanctions in order to provide a deterrent effect and support efforts to enforce Law Number 5 of 1990 concerning Conservation of Biological Natural Resources and Their Ecosystems. And the community in the conservation of natural resources plays a very important role in the success of the conservation effort itself. The participation and cooperation between the community and the government will certainly be a great synergy in conservation efforts. Abstrak. Perdagangan hewan dilindungi merupakan suatu tindakan pidana yang memiliki pengaruh besar bagi keseimbangan ekosistem makhluk hidup di alam. perdagangan ilegal hewan dilindungi salah satu dampaknya adalah terjadinya kepunahan pada hewan yang dilindungi tersebut. Perdagangan hewan liar dikatakan ilegal apabila tidak dimilikinya ijin resmi dari pemerintah serta Balai Konservasi Sumber Daya Alam. Tindak pidana perdagangan tersebut telah diatur dalam Undang Undang No. 5 Tahun 1990 Tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya. Pertama, Untuk memahami penegakan hukum tindak pidana perdagangan satwa dilindungi di wilayah kota Bandung. Kedua, Untuk memahami kebijakan pemerintah kota Bandung terhadap tindak pidana perdagangan satwa yang dilindungi. Penelitian ini penulis menggunakan metode pendekatan yuridis normatif. spesifikasi penelitian, penelitian ini bersifat deskriptif analitis. mengutamakan penelitian kepustakaan untuk memperoleh bahan pustaka sebagai data dasar, yang didukung dengan penelitian lapangan. Hasil dari penelitian ini adalah Penegakan hukum dalam berbagai bentuk bertujuan agar peraturan perundangan di bidang konservasi sumber daya alam hayati dan ekosistemnya dapat ditaati oleh seluruh lapisan masyarakat dan kepada pelanggarnya diberikan sanksi tegas agar memberikan efek jera dan mendukung upaya penegakan Undang-Undang Nomor 5 Tahun 1990 tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya. Serta masyarakat dalam konservasi sumber daya alam hayatu memegang peranan yang sangat penting dalam keberhasilan upaya konservasi itu sendiri. Peran serta dan kerjasama antara masyarakat dan pemerintah tentunya akan menjadi sinergi yang besar didalam upaya konservasi.